Take shelter - Nichols, Jeff, 1978-; Shannon, Michael, 1974-; Chastain, Jessica, 1977-; Stewart, Tova (Culver City, Calif. : Sony Pictures Home Entertainment, 2012)
After a man begins having disturbing visions of storms, he begins building a shelter in his family's yard to protect his wife and daughter.
Originally released as a motion picture in 2011.
Features: deleted scenes, commentary with Jeff Nichols & Michael Shannon, behind the scenes of "Take shelter," Q&A with Michael Shannon & Shea Whigham, BD-Live enabled.
Michael Shannon, Jessica Chastain, Tova Stewart, Shea Whigham, Katy Mixon.
MPAA rating: R.
Blu-ray disc, DTS-HD Master Audio 5.1.
This is a Blu-ray disc made for Blu-ray disc players and will not play in standard DVD players.
Keywords: Visions -- Drama; Mental illness -- Drama; Families -- Drama; Fiction films; Video recordings for the hearing impaired; Thriller films; Feature films